Лист К.Ґардецької до В.Дорошенка про перебування М.Грушевського у Криворівні (вступна стаття й публікація І.Гирича, Київ) - Гирич, І. (Український історичний журнал, 2021)
Оприлюднюється нове джерело, що розповідає про значення для української
культури і для творчої діяльності М.Грушевського села Криворівня на Гуцульщині. Наукова
новизна, висновки. У грушевськознавчий контекст уводиться досі невідомий лист-спогад
К.Ґардецької, в якому міститься інформація про перебування М.Грушевського у Криворівні.
Його авторка була донькою пароха місцевої церкви Різдва Пресвятої Богородиці та
громадського діяча О.Волянського, котрому належала ідея перетворити гуцульське село
на курорт для національної культурної еліти початку ХХ ст. Українська громадськість
намагалася формувати власне відпочинкове середовище за зразком польського Закопаного
чи російських Пущі-Водиці або Ворзеля під Києвом. Завдяки О.Волянському у Криворівні
в літні місяці оселялися відомі вчені, літератори, діячі, що стояли біля джерел національно-
визвольного руху, творили суспільно-культурні засади майбутньої Української революції 1917–
1921 рр. (В.Гнатюк, І.Франко, М.Грушевський, Леся Українка, Є.Тимченко, М.Коцюбинський,
О.Олесь, Г.Хоткевич, В.Дорошенко та ін.). Журналістка, активістка українського жіночого
руху в повоєнній Німеччині та у США К.Ґардецька наводить цікаві нюанси взаємин між
відпочивальниками у Криворівні, роки їх перебування тут, згадує про тих, хто облаштовував
побут приїжджих наддніпрянців у селах і містечках округи. Матеріали, викладені в листі, його
адресат В.Дорошенко збирався використати у книзі спогадів про М.Грушевського, яку, проте,
так і не встиг видати. A new source is published, which tells about the significance for Ukrainian culture and
for the creative activity of M.Hrushevskyі in the Carpathian village Kryvorivnіa. Scientific novelty
and conclusions. An unknown letter-memoir about M.Hrushevskyi’s stay in Kryvorivnia and his
intellectual environment there is introduced into scientific context for the first time. The “Hrushevskyi in
Kryvorivnia” topic has been studied in sufficient detail. Such local historians and Hrushevskyi scholars as
P.Arsenych, S.Pankova have covered it extensively. The letter to the prominent bibliographer and literary
critic V.Doroshenko contains an unknown memoir about Kryvorivnia and M.Hrushevskyi, written by
K.Gardetska, the daughter of O.Volianskyi, local pastor of the Nativity of the Blessed Virgin church, and
a well-known public figure. The latter had the idea to turn Kryvorivnia into a “holiday resort Mecca”
of the Ukrainian cultural elite in the early 20th century. Ukrainian activists did not want to fall behind
and seeked to create a Ukrainian cultural environment to counter the Polish and Russian equivalents,
like that of the Polish Zakopane, Russian Pushcha-Vodytsia or Vorzel near Kyiv. Due to O.Volianskyi’s
efforts, Kryvorivnia became a sought-after summer vacation spot for famous scientists, writers and public
figures, such as V.Hnatiuk, I.Franko, M.Hrushevskyi, Lesia Ukrainka, Ye.Tymchenko, M.Kotsiubynskyi,
O.Oles, H.Khotkevych, V.Doroshenko and many others, turning into a haven for people who stood at
the forefront of the Ukrainian national liberation movement and contributed to the establishment of
the socio-cultural foundations of the Ukrainian revolution of 1917–1921. K.Gardetska herself was also
a well-known public figure, journalist, and Ukrainian women’s rights activist in postwar Germany and
the United States. In her memoirs, she lists fascinating details of the relationships between Ukrainian
vacationers in Kryvorivnia, as well as the years of their stay. She mentions Ukrainians who helped visitors
from the Upper Dnipro region to settle in the nearby villages. V.Doroshenko was going to use these
materials in his book of memoirs about M.Hrushevskyi, which he never managed to publish.